Postscript: Reflections on the Cultural Policy Conference, Belfield, UCD, June 2014 - Quinn, Ruairi (Irish Journal of Arts Management and Cultural Policy, 2015)
Ruairi Quinn, Minister for Education (2011-14), offered a reflection on the achievements of Irish cultural policy since the foundation of the state and the challenges and opportunities facing the Irish cultural sector as it recovered from the impact of the 2008 economic collapse. Where do we begin, in the second decade of this century? Do we start to look for renewed directions for an Irish cultural policy that fits the contours of Ireland today? The answer must be yes.